Applying Cooperative Learning Using the Number Head Together Method in Teaching Balaghah: في تدريس البلاغة بمعهد دار العلوم العصري بندا أتشيه Number Head Together تطبيق مدخل التعلم التعاوني بأسلوب - Ashila, Muna; Syahminan, Syahminan; Ridha, Muhammad; Abdullah, Abdullah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2024)
Based on initial observations made by researcher at Dayah Modern Darul Ulum Banda Aceh, researcher found that students consider Balaghah as one of the most difficult subjects, and most students do not master a lot of vocabulary in the book, and this makes students feel bored and do not want to learn it so that the material is not well understood. This study aims to determine the effectiveness of the application of cooperative learning approach with Numbered Head Together model to improve students' ability to understand Balaghah and to know the activities of teachers and students when applying cooperative learning approach with Numbered Head Together model in teaching Balaghah. The research method used by researchers is the experimental method with the "One Group Pre-Test Post-Test Design" model. The researcher used direct observation, pretest and posttest as data collection methods. The results of this study are: (1) The application of cooperative learning approach in Numbered Head Together method is effective to improve students' ability to understand Balaghah. Because researchers obtained the results of the Wilcoxon Sigh Rank test showing that the results of the significance level Asymp. Sig. (2-tailed) < 0.001 which is smaller than the result of the significance level (Sig) 0.05. This indicates that the alternative hypothesis (Ha) is acceptable and the null hypothesis (H0) is rejected. (2) The activity of teacher and students in applying cooperative learning approach with Numbered Head Together model in teaching Balaghah is very good. The researcher obtained a value of P=90% for the observation of teacher and student activities. The value is in the range of 81 and 100% and this result shows that the activities of teachers and students during teaching and learning are very good.